Pendampingan Pemetaan Kebutuhan Ruang, Peningkatan Keamanan Bangunan dan Lingkungan Panti Rehabilitasi Gangguan Jiwa di Jakarta Utara - Ali, Abdullah; Juwono, Sudarmawan; Marlin, Syamsu (LPPM Universitas Bung Karno, 2023)
Community Service Activities (PkM) with partners from the Nurul Alam Paitama Foundation with Assistance in the Redesign of the Building and Environment of the Mental Disorders Rehabilitation Home in North Jakarta. This home is a form of service carried out by the community independently in the form of treatment for patients suffering from mental disorders using religious therapy methods. Currently, the home, which has an area of ​​696 m2 on 1,200 m2 of land, accommodates 27 patients who are served by 20 volunteer nurses. Existing spaces include a mosque as the main room and center for therapy activities, a secretariat room, living room and patient care area, kitchen, patient common room and other supports. The urgency of this Community Service activity, namely the need to improve the quality of buildings and the environment in the form of redesign in mentoring approaches and behavioral methods where space and facility needs are built, is dialogued with residents based on aspirations, space experiences, and also observed activities. As is known, the basic principle of mentoring itself is the empowerment of every potential that exists, both physical and non-physical. Thus, this program fully involves residents as the subject of a shared agenda. This involvement produces primary and secondary data for the need for redesign and placement of CCTV monitoring points in buildings and environments with their respective functions. The aim of PkM activities is as a form of devotional service in improving the quality of space by redesigning buildings and the environment to improve patient care and healing services, especially from the aspect of security and room comfort for residents. This condition supports conditioning and forming positive behavior for patients based on religious therapy methods so that sacredness becomes absolutely necessary.